Analisis Pesan Moral pada Film Miracle in Cell No. 7 Versi Indonesia: Studi Semiotika Analisis Pesan Moral Pada Film Miracle In Cell No.7 Versi Indonesia - putri handayani; Mochammad Rochim (UNISBA Press, 2023)
Abstract. The Indonesian version of Miracle In Cell No.7 is a 145-minute melodrama and family comedy released on September 8, 2022 The object of study of this study is the Indonesian version of the film Miracle in Cell No. 7, tells the story of Dodo Rozak who has a mental limitation (Disability) He has a child named Kartika. Qualitative research emphasizes the observation of a phenomenon and requires a keen instinct from the researcher. The object of this study is the film Miracle in Cell No. 7 which tells the story of Dodo Rozak who has a mental limitation or a disability. The paradigm that will be used in this study is constructivism. The method to be used semiotic analysis from Roland Barthles which examines connotative, denotative and myth. Research data collection techniques use interviews and documentation and search for data from journals, articles, theses, books, and online media. Researchers are interested in analyzing what moral messages the cast and director want to convey in this film to the audience or audience. As a result, researchers understand that every human being who has a deficiency who is born as a disabled person can also provide moral messages in the form of honesty, sincerity, resignation, patience, sincerity, helpfulness to humans who are born normal, the figure of a child raised by a disabled person grows up with a moral attitude of filial piety to the figure he loves, the emotional bond of father and son who love each other, From this film researchers can also know that the law is